Bases neurobiológicas de la rehabilitación (2014)
ABSTRACT: Neurological rehabilitation treatments are based on an intrinsic property of the Central Nervous System: to adapt to changes in their environment. Cerebral Plasticity involves structural and functional changes in neurons and neural networks and to their understanding is necessary to consider what happens at different levels, considering also genetic and non-genetic factors that may influence these processes. There are currently electrophysiological and images that allow the study of Brain Plasticity in healthy humans and with brain injuries. Greater understanding the phenomena that occur in the nervous system after an injury may enable therapeutic application tailored to the needs of each individual.